Upstream. B2+: teacher's book - Evans V. Virginia (Newbury, Express Publishing, 2017)
Upstream Upper Intermediate B2+ is a modular secondary-level course for learners of the English language at upper-intermediate level. The series combines active English learning with a variety of lively topics presented in themed units. Key Features theme-based units from a wide variety of authentic sources in five modules a variety of cross-cultural topics systematic development of all four language skills through realistic challenging tasks which encourage the learner's personal engagement lexical exercises practising and activating all essential vocabulary including collocations, idioms and fixed phrases, prepositions, phrasal verbs and word formation a variety of authentic stimulating reading and listening tasks a wide range of speaking activities realistic, stimulating dialogues featuring people in everyday situationsgrammar sections covering all major grammatical areas plus a Grammar.